Fertilization triggers unmasking of maternal mRNAs in sea urchin eggs. - Grainger, J L (1987)
Fertilization of sea urchin eggs results in a large increase in the rate of protein synthesis which is mediated by the translation of stored maternal mRNA. The masked message hypothesis suggests that messenger ribonucleoprotein particles (mRNPs) from unfertilized eggs are translationally inactive and that fertilization results in alterations of the mRNPs such that they become translationally active. Previous workers have isolated egg mRNPs by sucrose gradient centrifugation and have assayed their translational activity in heterologous cell-free systems. The conflicting results they obtained are probably due to the sensitivity of mRNPs to artifactual activation and inactivation. Previously, we demonstrated that unfractionated mRNPs in a sea urchin cell-free translation system were translationally inactive. Now, using large-pore gel filtration chromatography, we partially purified egg mRNPs while retaining their translationally repressed state. Polysomal mRNPs from fertilized eggs isolated under the same conditions were translationally active. The changes in the pattern of proteins synthesized by fractionated unfertilized and fertilized mRNPs in vitro were similar to those changes observed in vivo. Treatment of egg mRNPs with buffers containing high salt and EDTA, followed by rechromatography, resulted in the activation of the mRNPs and the release of an inhibitor of translation from the mRNPs. Analysis of the inhibitory fraction on one-dimensional sodium dodecyl sulfate gels indicated that this fraction contains a complex set of proteins, several of which were released from high-salt-EDTA-activated mRNPs and not from inactive low-salt control mRNPs. One of the released proteins may be responsible for the repression of egg mRNPs in vitro and be involved in the unmasking of mRNPs at fertilization.